2017
DOI: 10.1016/j.biochi.2016.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Homeostatic effects of exercise and sleep on metabolic processes in mice with an overexpressed skeletal muscle clock

Abstract: Brain and muscle-ARNT-like factor (Bmal1/BMAL1) is an essential transcriptional/translational factor of circadian clocks. Loss of function of Bmal1/BMAL1 is highly disruptive to physiological and behavioral processes. In light of these previous findings, we examined if transgenic overexpression of Bmal1/BMAL1 in skeletal muscle could alter metabolic processes. First, we characterized in vivo and ex vivo metabolic phenotypes of muscle overexpressed mice (male and female) compared to wild-type littermates (WT). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…The antiandrogen Flutamide decreases the treadmill endurance of rats, but does not change O 2max and running economy 26 . Here, the exercise-induced submaximal O 2 and CO 2 up to O 2max were similar between sexes, as previously described 11 , 12 , 27 . Only one study demonstrated increased female submaximal O 2 during treadmill test, which further reinforces the hypothesis of females’ worst running economy 27 .…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The antiandrogen Flutamide decreases the treadmill endurance of rats, but does not change O 2max and running economy 26 . Here, the exercise-induced submaximal O 2 and CO 2 up to O 2max were similar between sexes, as previously described 11 , 12 , 27 . Only one study demonstrated increased female submaximal O 2 during treadmill test, which further reinforces the hypothesis of females’ worst running economy 27 .…”
Section: Discussionsupporting
confidence: 81%
“…The minor representation of females also translates into less knowledge about the biology of exercise in this sex. So far, the main features of sexual dimorphism important for exercise described in rodents are differences in skeletal muscle kinetics and fiber-type composition 10 and energy metabolism 11 , 12 . In fact, the biological mechanisms underlying the benefits of exercise were investigated in numerous animal studies in a laboratory setting, with a strong tendency to only use males probably to avoid dealing with the possible influence of the menstrual/estrous cycle 9 , 13 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, whole body deletions of other circadian factors such as Per1 and Per2 ( Shiromani et al, 2004 ), and Cry1 and Cry2 ( Wisor et al, 2008 ), do not have similar effects on sleep. Other potential contributors could be related to changes in muscle metabolism as Bmal1 metabolic phenotypes have been reported in both muscle mouse-lines used here ( Harfmann et al, 2016 ; Brager et al, 2017 ).…”
Section: Introductionmentioning
confidence: 85%
“…Thus, these results suggest an important role for skeletal muscle in sleep regulation, implying that Bmal1 -dependent processes in skeletal muscle may be useful therapeutic targets for sleep disorders. In an effort to investigate the therapeutic potential of muscle Bmal1 , we examined sleep architecture in wild type mice harboring either the brain or muscle-specific ( Brager et al, 2017 ) Bmal1 transgene. In these mice, transgene expression is in addition to endogenous Bmal1 expression.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to weight gain, altered circadian timing in skeletal muscle could contribute to reduced muscle insulin sensitivity. For example, overexpression of the core clock gene, brain and muscle-ARNT-like factor (BMAL1) in skeletal muscle results in decreased insulin-stimulated skeletal-muscle glucose uptake during acute sleep loss in mice [64]. These findings suggest that disruption of the skeletal-muscle circadian clocks can contribute to decreased skeletal-muscle insulin sensitivity during sleep loss.…”
Section: Ad Libitum Weekend Recovery Sleep Failed To Prevent Reduced mentioning
confidence: 99%